The Modified Ilioinguinal and Anterior Intrapelvic Approaches for Acetabular Fracture Fixation: Indications, Quality of Reduction, and Early Outcome. (February 2015) - Chesser, Tim J. S.; Eardley, Will; Mattin, Andrew; Lindh, Amy M.; Acharya, Mehool; Ward, Anthony J.
Abstract : Objectives: Traditionally, the anterior surgical approach of choice for acetabular reconstruction was ilioinguinal. There has been an increasing usage of the midline "Stoppa" or "anterior intrapelvic approach." The aim is to report the techniques, early results (minimum 1 year), and complications of anterior approaches for acetabular reconstruction. Design: Retrospective case-note review. Setting: Pelvic and acetabular tertiary center. Patients: A consecutive series of acetabular fractures treated at 1 tertiary specialist unit were retrospectively reviewed. The fracture patterns, incisions used, intraoperative and postoperative complications, reduction achieved (measured on postoperative radiographs and computed tomography scans), and early postoperative results (minimum 1-year follow-up), were recorded. Main Outcome Measurements: Postoperative reduction (measured by postoperative plain radiographs and computed tomography). Results: Of 160 consecutive patients who underwent acetabular reconstruction, 56 (mean age, 44 years) underwent reconstruction using only anterior approaches (mean of 7 days after injury). Iatrogenic complications, postoperative infection, arthritis, and avascular necrosis rates are comparable with the literature. Overall, anatomic reduction was seen in 71% of cases and concentric reconstruction of the dome in over 90%. Thirty-six of the 56 patients (64%) were symptom-free at the latest follow-up and 34 (61%) had returned to work. Conclusions: The results reported suggest the use of dual approaches using the lateral 2 windows, and/or a midline anterior intrapelvic approach in anterior acetabular reconstructions has a relatively low complication rate and can lead to anatomic reconstructions in 71%. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.